INVESTIGATING CHURCH BRANDING INFLUENCE TOWARDS CHURCH PARTICIPATION (CASE STUDY: HILLSONG CHURCH BALI) - Wijaya, Ida Ayu Yesanya; Lapian, S.L.H.V. Joyce; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Branding has been used as one of marketing strategy not only by profit organizations but also non-profit organizations. Thus, church also uses branding as one of its marketing strategy to enhance, promote, and to reach out to their market which is the congregations by creating their own brand that represents their style, value, characters, and uniqueness. The researcher conducted this research to investigate whether the church branding has influence towards church participation. This study uses qualitative method with exploratory approach. Meanwhile in-depth interview is used to collect the data among the respondents which are Hillsong Church Bali participants. Findings of this research shows that Hillsong church branding influence Hillsong Church Bali participations in many aspects rapidly and significantly such as church growth, increasing number of service attendance and committed volunteers. From the results, it is recommended for Hillsong Church Bali to keep up with their service standard and equip the leaders, workers, and volunteers through Hillsong Church programs. Hillsong Church Bali also needs to improve its system and management by applying Hillsong churchâ€™s system and management in order to perform better.Â Keywords: church branding, church participation